The military-technical revolution of the ХХI st century (Philosophical and analytical review) - Korostylov, Henadii L.; Dolska, Olga; Dezhong, Wang; Protsenko, Andrii; Makieshyna, Yuliia (University of Zulia, 2021)
The article discusses the history of the military-technical revolution, revealing its main characteristics. It was interesting to explain to others theconnection between the revolution and the technical and technological structure ofsociety, on the one hand, and the changes in modern warfare, its timing, the scale of the deployment of hostilities, on the other hand. The study is based on the methodology of systems analysis, as well as the use of logical generalization, synthesis, and abstraction. The authors rely on a wide range of illustrative material, which allowed to show the changes of the sixth military-technological revolution. The nature of the use of unmanned aerial vehicles in modern warfare is considered factual material. Based on specifi material, it is argued that the nature of modern warfare is hybrid in nature, but this hybridization itself is heterogeneous. Possible options for waging war and using certain equipment are shown. Based on analytical research, the authors focused on the transformation’s characteristic of modern wars. It is concluded that there is a transition period between the sixth and seventh technical-military revolutions that demand future interdisciplinary research.
Keywords: military-technical revolution; hybrid warfare; technique; science